Tingkat Tingkat Kematangan Sistem Informasi Manajemen Aset (SIMA) Institut Pertanian Bogor Versi Beta Menggunakan Cobit 4.1: Maturity Level Asset Management Information System (SIMA) IPB University Beta Version Using Cobit 4.1 - Firdaus, Hasan; Erizal, Erizal; Hermadi, Irman (Jurnal Aplikasi Bisnis dan Manajemen, 2020)
Inadequate asset management in non-profit organizations, in this case, Higher Education (PT), will harm the value of the potential benefits that can be obtained from those assets. SIMA IPB is the application of Information Technology (IT) which is expected to be able to support the achievement of accountability in the environment of IPB. In this research, the maturity level analysis of SIMA IPB uses the Framework of Control for Information and Related Technology 4.1 (COBIT 4.1), which is one of the tools used to see existing IT governance. COBIT has four domains, namely Plan and Organization (PO), Acquisition and Implementation (AI), Delivery and Support (DS), and Monitoring and Evaluation (ME). The results of this study were carried out in the PO, AI, DS and ME framework domain based on the maturity level of the COBIT 4.1 framework illustrated in the spider chart. The results found that the level of IT maturity in SIMA IPB Beta Version at Level 4 (managed) with an average maturity index (PO, 3.66), (AI, 3.39), (DS, 3.59), (ME, 3.54), and the gap value (gap) with an average value of 0.84, for the PO domain at level 4 (managed), AI domain level 3 (defined), DS level 4 (managed) domain and ME level 4 (managed) domain.Keywords: COBIT, maturity level, SIMA, information technology